Alokasi Dana Amanah Pemberdayaan Masyarakat Lembaga DAPM Kecamatan Konda Dalam Persfektif Hukum Ekonomi - Abdul Wahid Mongkito; Muhamad Turmudi; Andi Dwi Indah Putri (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
Micro-enterprises are one of the components that have a large enough contribution to create jobs in Indonesia, Micro, Small and Medium Enterprises (MSMEs) contributed Rp. 8,573.9 trillion to the Indonesian economy in 2020. However, the potential possessed by MSMEs is not without its weaknesses. especially in terms of capital. To overcome this, the government launched a revolving fund program called the Community Empowerment Allocation Fund (DAPM). The type of research carried out is qualitative research with case study methods on the management of the DAPM program in Konda District. The data used are primary and secondary data through observation, interviews and document studies. The results of this study indicate the allocation of DAPM revolving funds in Konda District in two group categories, namely the Women's Savings and Loans (SPP) and the Productive Economic Business Group with a payback period of up to 20 months. The DAPM institution takes a 1.5% service benefit in monthly installments, as well as a fine if you are late paying off the installments. This practice is contrary to sharia economic law, which is included in usury qardh and usury nasi'ah. The percentage of the population of Konda District reaching 97.83 Muslims needs to be given an alternative contract, based on in-depth research on the community's need for revolving funds, the researcher offers it in the form of Murabahah and Istisna contracts for buying and selling transactions, as well as Mudharaba and Musyarakah contracts for business development.